Morphology Control in Block Copolymer Films Using Mixed Solvent Vapors - Gotrik, Kevin W.; Hannon, Adam F.; Son, Jeong Gon; Keller, Brent; Alexander-Katz, Alfredo; Ross, Caroline A. (AMER CHEMICAL SOC, 2012)
Solvent vapor annealing of block copolymer thin films can produce a range of morphologies different from the equilibrium bulk morphology. By systematically varying the flow rate of two different solvent vapors (toluene and n-heptane) and an inert gas, phase maps showing the morphology versus vapor pressure of the solvents were constructed for 45 kg/mol polystyrene-block-polydimethylsiloxane diblock copolymer films of different thicknesses. The final morphology was correlated with the swelling of the block copolymer and homopolymer films and the solvent vapor annealing conditions. Self-consistent field theory is used to model the effects of solvent swelling. These results provide a framework for predicting the range of morphologies available under different solvent vapor conditions, which is important in lithographic applications where precise control of morphology and critical dimensions are essential.
Keywords: THIN-FILMS; ORDERED STRUCTURE; POLYMER-SOLUTIONS; PHASE-BEHAVIOR; THERMODYNAMICS; POLYSTYRENE; TEMPERATURE; CHAIN